Academic Half-Day Education Experience in Post-graduate Medical Training: A Scoping Review of Characteristics and Learner Outcomes - Choe, Myong Sun; Huffman, Lynne C.; Feldman, Heidi M.; Hubner, Lauren M. (Frontiers in Medicine, 2022)
Background The academic half-day (AHD) has grown in popularity for medical education because it intends to provide learners with uninterrupted, immersive learning time that may promote participant attendance, engagement, and knowledge. Little is known about the extent of use, forms, or effectiveness of AHD in post-graduate medical education. This scoping review summarizes existing literature and describes the learning outcomes, according to the Kirkpatrick model of learning evaluation, of AHD experiences on post-graduate medical trainees. Methods Authors used Arksey and O’Malley’s methodological framework, searching electronic scientific literature databases from the years of 1977-2019 with relevant key terms and identifying 735 papers. Two independent raters completed title/abstract screening and then extracted pertinent data from papers meeting specified criteria. Results Authors identified 38 relevant papers published in English, originating from programs in US (n=19) and Canada (n=19), spanning 4 disciplines: Medicine (n=17, 45%), Pediatrics (n=10, 26%), Critical Care/Surgery (n=9, 24%), Radiology (n=2, 5%). A majority (n=33, 87%) described specific educational experiences; most focused on residents only (n=27). The educational experiences included various teaching strategies; few were didactics only (n=4) and most were multi-modal including simulation, case-based learning, problem-based learning, and/or self-directed online study. AHD size ranged from 5-364 participants (median 39). AHD length was 1.5-6 hours (median 3). Required resources were inconsistently described. When evaluations of the specific educational experience were reported (n=35 studies), the majority of studies used weak research designs (e.g., one group, pre/post-test, n=19); few studies used strong research designs (e.g., randomized controlled trial, n=2). Positive effects of AHD ranged across Kirkpatrick levels 1-3 learner outcomes. Conclusions The composition and content of AHD in post-graduate medical education vary. Few studies of AHD use stringent research designs, and none include learner outcome measures at the highest Kirkpatrick level (i.e., level 4 results/patient outcomes). A consensus definition and further high-quality research on AHD in post-graduate medical education is needed.